Culture of Productivity in Higher Education Institutions in Indonesia - Sumaryono, Agustinus; Fitrian, Farhan; R. Madhakomala, R. Madhakomala (Jurnal Edusci, 2025)
This research seeks to fill the gap by exploring productivity culture theory and applying in concretely in the Indonesian context. Thus, this research is expected to provide new insights and significantly contribute to the design of more effective and inclusive policies to improve the productivity culture in higher education in Indonesia. This research uses a descriptive research type method to better understand productivity culture from various theoretical and practical perspectives. This research shows that productivity culture in higher education is very important. it can be found that there are several challenges and problems of productivity culture in Indonesia, including Inequality of Access, inequality of quality, lack of access, and problems from input, process, and output of higher education in Indonesia. In order to overcome the problems above, it is necessary to have mutual cooperation and collaboration from all parts of the nation as the key to implementing several alternative solutions, including the Use of government education fund allocation for research, The Establishment of Writer University, Collaboration of Indonesian universities with top world universities, Improving the quality and management of educators and education personnel in higher education. The awareness of productivity culture is a concern and requires a balance between input, process, and output quality in higher education. This study may not consider some factors that can influence the increasing productivity culture, such as geographic conditions and cultural diversity in various regions of Indonesia. Further research with a conceptual approach can provide more comprehensive insight into productivity culture problems in higher education in Indonesia.